2022
DOI: 10.3389/fimmu.2022.951984
|View full text |Cite
|
Sign up to set email alerts
|

2B and 3C Proteins of Senecavirus A Antagonize the Antiviral Activity of DDX21 via the Caspase-Dependent Degradation of DDX21

Abstract: Senecavirus A (SVA), also known as Seneca Valley virus, is a recently discovered picornavirus that can cause swine vesicular disease, posing a great threat to the global swine industry. It can replicate efficiently in cells, but the molecular mechanism remains poorly understood. This study determined the host’s differentially expressed proteins (DEPs) during SVA infection using dimethyl labeling based on quantitative proteomics. Among the DE proteins, DDX21, a member of the DEAD (Asp-Glu-Ala-Asp)-box RNA helic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…The subcellular distribution of DDX21 into nucleolus is required for the RNA unwinding ( Song et al, 2017 ). DDX21 regulates viral replication through many ways, including inhibiting viral genome replication and prohibiting virus replication ( Watanabe et al, 2009 ; Abdullah et al, 2021 ; Li et al, 2022b ; Zhao et al, 2022 ). DDX21 interacts with rRNAs and snoRNAs to facilitate transcription and processing ( Flores-Rozas and Hurwitz, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subcellular distribution of DDX21 into nucleolus is required for the RNA unwinding ( Song et al, 2017 ). DDX21 regulates viral replication through many ways, including inhibiting viral genome replication and prohibiting virus replication ( Watanabe et al, 2009 ; Abdullah et al, 2021 ; Li et al, 2022b ; Zhao et al, 2022 ). DDX21 interacts with rRNAs and snoRNAs to facilitate transcription and processing ( Flores-Rozas and Hurwitz, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…DDX21 redistributes from the nucleus to the cytoplasm for inducing innate immune responses during dengue virus infection ( Dong et al, 2016 ). Moreover, DDX21 facilitates redistribution to the cytoplasm to reduce IFN-β production through disrupting the DDX1-DDX21-DHX36 complex during infection ( Li et al, 2022a ; Zhao et al, 2022 ). Herein, we demonstrated that DDX21 redistributed to the cytoplasm from the nucleolus during PCV2 infection ( Figure 1 ), suggesting that PCV2 infection induces DDX21 relocation to inhibit innate immunity and facilitate viral replication; however, the underlying mechanisms need further study.…”
Section: Discussionmentioning
confidence: 99%
“…3389/fmicb.2023.1235620 Frontiers in Microbiology 07 frontiersin.org system attacks (Qian et al, 2017;Xue et al, 2018a,b;Wen et al, 2019). Additionally, SVV 3C pro affects various processes, such as cell mRNA translation (Xue et al, 2020;Song et al, 2021Song et al, , 2022bWen et al, 2022;Zhao et al, 2022), Pyroptosis (Wen et al, 2021a), apoptosis (Liu et al, 2019;Zhao et al, 2023), and autophagy (Wen et al, 2021b;Zhao et al, 2023), which may facilitate virus replication. Notably, this protease interacts with many crucial host proteins, cleaving them to exploit host cell resources while avoiding or mitigating immune responses (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…DDX21 mediates innate immunity and regulates the viral replication of viruses such as foot-and-mouth disease virus (FMDV) (Abdullah et al, 2021), dengue virus (DENV) (Dong et al, 2016) and Borna disease virus (BDV) (Watanabe et al, 2009). Furthermore, DDX21 has been shown to inhibit SVV replication, but its effects can be weakened by SVV 3C pro , which induces caspase-dependent degradation of DDX21 and suppresses host antiviral immunity, limiting the cell antiviral response (Zhao et al, 2022). DHX30, a DEAD family member, contributes to the biosynthesis of mitochondrial ribosomes.…”
Section: Role Of 3c Proteases In Regulating Mrnamentioning
confidence: 99%
“…The mutated 3C failed to induce the degradation of DDX21. All of these suggested that the protease activity of 3C protein was necessary for the degradation of DDX21, which contributed to SVA evading the antiviral effect of DDX21 ( 67 ).…”
Section: Ddx21mentioning
confidence: 99%